If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(h + -8) = 0 Reorder the terms: 7(-8 + h) = 0 (-8 * 7 + h * 7) = 0 (-56 + 7h) = 0 Solving -56 + 7h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 7h = 0 + 56 Combine like terms: -56 + 56 = 0 0 + 7h = 0 + 56 7h = 0 + 56 Combine like terms: 0 + 56 = 56 7h = 56 Divide each side by '7'. h = 8 Simplifying h = 8
| 5x+29=74 | | 64/8-3n=5n | | 2(4+5x)=48 | | 6x-33=57 | | 27-4n=1 | | n-37=43 | | 3(1+7x)=45 | | 4d+7=6d | | 8x+8=8x+13 | | 2x^2+9x+4=o | | 8x+34=138 | | -47+12x=25 | | x-9=3x+7 | | 6/7+5/6 | | 2(5x+2)=94 | | -4+12=13x-12x | | 2x-4=2000 | | 4(7+6x)=100 | | -82+8x=30 | | 5(4y-3)=11 | | .05x+.11(2x+20000)=20830 | | 35+11x=200 | | solvemy+11-with=nform | | 2(6x+10)=116 | | 7k+3=2+5k | | 5x=3/8 | | 1108/27=x | | -69+5x=21 | | p=2l+2fort | | 7(4+5x)=168 | | -30+3x=12 | | 9x+7=69+x |